Hypertriglyceridemia in a family with a high incidence of type II diabetes - Semprún de Fereira, M.; Ryder, Elena; García de Zambrano, N.; Campos, G. (Investigación Clínica, 2013)
Fourteen individuals from two generations of a family with a high incidence of type 11 diabetes were studied. Six out of twelve siblings (50%) developed diabetes between 24 and 45 years of age. They were the product of a non diabetic father, whose family had a high incidence of diabetes, and diabetic mother (age of onset = 52 years) whose family history was negative for diabetes. The duration of diabetes in the siblings at the time of the study ranged from 3 to 13 years. Only one required insulin for control of the hyperglycemia while the others were treated with oral hypoglycemic agents and/or diet. Hypertriglyceridemia was present ind 5 of the 6 diabetic sibligs (83%) and in several other nondiabetic members of the family and was highly correlated with age (r =0.86; p < 0.01), but not with the body mass index or diet. It is proposed that a common genetic trait might account for both metabolic dysfunctions.